POTENSI LIMBAH JERAMI PADI DAN DAUN SINGKONG UNTUK MENDUKUNG PROGRAM PEMBIBITAN SAPI PO (PERANAKAN ONGOLE) DI DESA SIDOMUKTI KECAMATAN TANJUNG SARI KABUPATN LAMPUNG SELATAN - Maulana Aziz; Muhtarudin .; Yusuf Widodo (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
The study aimed to know the production of waste of rice straw and cassava leaves and the carrying capacity of cattlein Sidomukti Village, Tanjung Sari Sub-District, South Lampung District based on the potency of waste of ricestraw and cassava leaves.This study was conducted in May until September 2013 located in Sidomukti Village, Tanjung Sari Sub-District,South Lampung District. The study used survey methode of purposeive sampling. Data used in this study consistedof primer and secondary data. The analysis of water value was done in Laboratory of Nutrition and AnimalFeedstuff Animal Husbandry Department, Faculty of Agriculture, University of Lampung.The result of this study showed that the wide of rice and cassava field in Sidomukti Village the forage waste as widewas 43 ha and 116 ha. Totally as much as 469.669,81 kg/year (46,96) ton/year for dry matter and protein as27.511,677 kg/th (2,75 ton/th). The waste production of rice straw and leaves cassava to carrying capacity PO studcattle seed as 53 UT/year.